Acid stability of the kinetically stable alkaline serine protease possessing polyproline II fold - Rohamare, Sonali; Javdekar, Vaishali; Dalal, Sayli A.; Nareddy, Pavan Kumar; Swamy, Musti J.; Gaikwad, Sushama M. (Protein Journal, 2015)
The kinetically stable alkaline serine protease from Nocardiopsis sp.; NprotI, possessing polyproline II fold (PPII) was characterized for its pH stability using proteolytic assay, fluorescence and Circular Dichroism (CD) spectroscopy, and Differential Scanning Calorimetry (DSC). NprotI was found to be functionally stable when incubated at pH 1.0, even after 24 h, while after incubation at pH 10.0, drastic loss in the activity was observed. The enzyme showed enhanced activity after incubation at pH 1.0 and 3.0, at higher temperature (50-60 A degrees C). NprotI maintained the overall PPII fold in broad pH range as seen using far UV CD spectroscopy. The PPII fold of NprotI incubated at pH 1.0 remained fairly intact up to 70 A degrees C. Based on the isodichroic point and T-m values revealed by secondary structural transitions, different modes of thermal denaturation at pH 1.0, 5.0 and 10.0 were observed. DSC studies of NprotI incubated at acidic pH (pH 1.0-5.0) showed T-m values in the range of 74-76 A degrees C while significant decrease in T-m (63.8 A degrees C) was observed at pH 10.0. NprotI could be chemically denatured at pH 5.0 (stability pH) only with guanidine thiocynate. NprotI can be classified as type III protein among the three acid denatured states. Acid tolerant and thermostable NprotI can serve as a potential candidate for biotechnological applications.
Keywords: Acid stability; DSC; Kinetic stability; Polyproline fold; Protease; Thermal unfolding